Sounds of Crossing : Music, Migration, and the Aural Poetics of Huapango Arribeño - Chávez, Alex E., 1982- (Book collections on Project MUSE., 2017)
Alex E. Chávez explores the contemporary politics of Mexican migrant cultural expression manifest in huapango arribeño, a musical genre from north-central Mexico that helps Mexicans build communities on both sides of the US border and give voice to the transnational migrant experience.